TALAQ TIGA: ANALISIS TERHADAP PENGHAKIMAN MAHKAMAH SYARIAH - Abdullah, Raihanah (Jurnal Syariah, 2019)
Muslim jurists classify the pronouncement of triple talaq at the same sitting as talaq al-bid’ah. Some jurist are of the view that this form of talaq is revocable while others hold that it is irrevocable as soon as it is pronounced. In Malaysia, there is no provision regarding the above matter under the Islamic Family Law Enacments and so, if the case arises, the Court will decide upon it according to the Hukum Syara ’. This article analyses the judgement of the Shariah Courts pertaining to the issue of triple talaq.